Editorial - Câmara, Gabriel Guerra; Lopes, Ricardo Cortez; De Freitas, Gabriela Ramão; de Gonçalves, Fernando Gonçalves; Hubert, Stephan; Casalotti, Bruno; Karpowicz, Alexandre (Revista Contraponto, 2016)
Confira o nosso editorial!